Encanto: A Broken Latino Culture in Popular Literature - Tyara Riszky Pratidina; Aris Wuryantoro; Lusia Kristiasih Dwi Purnomosasi (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2023)
The aim of this article is to analyze Heroine of Encanto who breaks the stereotype of Latino culture. The theory of culture is “The Seven Element of Culture” to find out the element of culture that shows stereotypes of Latino. The methods used in this article is qualitative methods with data condensation, data display, and conclusion drawing or verification. The result shows two aspect culture, there are social organization and custom and traditions, which give evidences of breaking the stereotype of Latino culture. Two of them confirm the female character and the new world view as young generation change the old tradition as the stereotype.